Aggression among adolescents: The role of emotion regulation - Purwadi Purwadi; Said Alhadi; Agus Supriyanto; Wahyu Nanda Eka Saputra; Siti Muyana; Amien Wahyudi (Universitas Ahmad Dahlan, 2020)
Aggressive behavior expressed by adolescents is a worrying phenomenon. There might be circumstances underlying this aggression, such as adaptive or maladaptive emotional conditions. To study the role of emotion regulation toward aggression on adolescents, the researchers performed quantitative correlational research toward 943 secondary school students in the Special Province of Yogyakarta. Data was collected using an emotion regulation scale and an aggression scale. The data was then examined using multiple regression analysis to observe the correlation among variables. The result of this research shows that emotion regulation significantly influences the development of aggression. Further analysis of two strategies on emotion regulation shows that excessive emotion suppression affects the development of aggression, while emotion regulation through cognitive appraisal does not. The implication of this research is emotion regulation through emotion suppression has a more significant influence on the development of aggression on adolescents compared to cognitive appraisal. The stronger emotion suppression method is employed, the higher the level of aggression might be developed.